The Nexus of Participation, Co-Production of Knowledge, and Community Resilience in Waste Management in Bulusan - Yoga Ramadhani; Putri Alyaa Safira; Gertha Maria Gultom; Bintang Corvi Diphda; Angelique Kishiola Prima Foraihmbarasi; Rayhan Aulia Prakoso; Yasa Palaguna Umar (Goodwood Publishing, 2026)
Purpose: This study evaluates the reasons for the failure of technological interventions to foster community resilience within the “Sampah Terkelola, Lingkungan Terjaga” program in Bulusan Village. Research Methodology: Using a qualitative case study, data were gathered through participant observation (July–August 2025), semi-structured interviews, and document analysis. The Community Capitals Framework (CCF), participation theory, and knowledge co-production served as primary diagnostic lenses. Results: Findings indicate that while the program bolstered built and human capital through infrastructure, it neglected financial and political capital. This imbalance, driven by top-down planning and the lack of a revenue model, led to the immediate stagnation of the local Waste Bank post-intervention. Conclusions: Sustainable waste management requires a shift in focus from technology transfer to the co-production of managerial knowledge and the institutionalization of governance structures that balance all community capital. Limitations: This study is restricted to a short-term qualitative assessment of a single village and lacks longitudinal data. Contributions: This research advances the environmental sociology and rural development literature by establishing the CCF as a critical evaluative tool for predicting the institutional durability of community-based interventions. This explicitly demonstrates that social capital integration is a prerequisite for, rather than a byproduct of, technological success in waste management.